2020
DOI: 10.1155/2020/3278081
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Interleukin Gene Polymorphisms and Risks of Developing Extremity Posttraumatic Osteomyelitis in Chinese Han Population

Abstract: This case-control study aimed to investigate potential associations between interleukin (IL) gene polymorphisms and the risks of developing extremity posttraumatic osteomyelitis (PTOM) in Chinese Han population. Altogether, 189 PTOM patients and 200 healthy controls were genotyped of IL-1α (rs17561, rs1800587), IL-1β (rs16944, rs1143627, rs1143634, rs2853550), IL-1RN (rs4251961, rs419598, rs315951), IL-4 (rs2243248, rs2243250), IL-6 (rs1800795, rs1800796, rs1800797), IL-8 (rs4073, rs2227306, rs2227307), IL-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 26 publications
1
17
1
Order By: Relevance
“…The result of IL1A rs1800587 regarded as a risk factor for osteomyelitis was consistent with the outcome reported by Asensi et al (2003). However, no significant difference was observed between patients with osteomyelitis and healthy controls regarding the individual alleles and genotypes of IL-1α rs1800587 in the studies of Jiang et al (2020) and Osman et al (2016). Osman et al (2015) have reported that the population with the C allele or CC genotype might increase the susceptibility to hematogenous osteomyelitis, whereas the T allele or CT genotype could act as a protector factor.…”
Section: Cytokine-related Proteinssupporting
confidence: 84%
See 4 more Smart Citations
“…The result of IL1A rs1800587 regarded as a risk factor for osteomyelitis was consistent with the outcome reported by Asensi et al (2003). However, no significant difference was observed between patients with osteomyelitis and healthy controls regarding the individual alleles and genotypes of IL-1α rs1800587 in the studies of Jiang et al (2020) and Osman et al (2016). Osman et al (2015) have reported that the population with the C allele or CC genotype might increase the susceptibility to hematogenous osteomyelitis, whereas the T allele or CT genotype could act as a protector factor.…”
Section: Cytokine-related Proteinssupporting
confidence: 84%
“…Osman et al (2016) have also revealed that the AA genotype of rs16944 in IL1β could be a risk factor, whereas the allele G and GG genotype of this SNP were considered a protector against hematogenous osteomyelitis among Saudis. However, this result was contrary to the conclusion of the study by Jiang et al (2020). Zhao et al (2020) have recently reported that the mutant allele A in rs2430561 might be a risk factor of posttraumatic osteomyelitis, and individuals with the AT genotype in this gene might have a higher risk of developing posttraumatic osteomyelitis.…”
Section: Cytokine-related Proteinscontrasting
confidence: 75%
See 3 more Smart Citations